2011
DOI: 10.1002/bbb.278
|View full text |Cite
|
Sign up to set email alerts
|

The energy balance of soybean biodiesel in Brazil: a case study

Abstract: Like any other manufactured product, the production of biofuels involves the consumption of several inputs along its production chain. Energy balance results are often contradictory mainly due to differences in the methodologies used for their calculation. Despite the lack of a national database, this paper is a fi rst estimate of the energy balance of biodiesel from soybean in Brazil. Data collected from fi ve plantations located in the state of São Paulo, with a total production of 2000 metric tonnes, along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 15 publications
0
19
1
1
Order By: Relevance
“…A farm-gate boundary energy analysis provides the first step to insight toward the evaluation of sustainability for the biofuel production system. Murphy et al (2011a) and Mourad and Walter (2011) found that feedstock production accounted for between 11% and 36% of the total energy inputs in biofuel production where approximately 12% was variable based on geographic location.…”
Section: Cumulative Energy Demand and Net Energy Analysismentioning
confidence: 99%
“…A farm-gate boundary energy analysis provides the first step to insight toward the evaluation of sustainability for the biofuel production system. Murphy et al (2011a) and Mourad and Walter (2011) found that feedstock production accounted for between 11% and 36% of the total energy inputs in biofuel production where approximately 12% was variable based on geographic location.…”
Section: Cumulative Energy Demand and Net Energy Analysismentioning
confidence: 99%
“…From the energy lifecycle analysis viewpoint, it is necessary to carry out the calculation of net energy ratio (NER) for the microalgal biofuel production chain. The NER of a system has been defined as the ratio of the total energy produced (biodiesel, ethanol, and methane) over the energy content of construction and material plus the energy required for all plant operations . The higher the net energy ratio, the greater the efficiency of the production chain.…”
Section: Is It Always Necessary To Produce Biodiesel And/or Ethanol Fmentioning
confidence: 99%
“…Th e NER of a system has been defi ned as the ratio of the total energy produced (biodiesel, ethanol, and methane) over the energy content of construction and material plus the energy required for all plant operations. 37 Th e higher the for instance, to energy grids, to further improve the economics of the combined system. 40 However, the potential balance of algal biofuel production with regard to energy input and output ranges widely depending on the cultivation systems, energy savings realized by the by-products, such as glycerol, and so on.…”
Section: Is It Always Necessary To Produce Biodiesel And/or Ethanol Fmentioning
confidence: 99%
“…In comparison, 390,000 BTUs of energy are consumed during the processing of one gallon of Biodiesel from soybeans: 350,000 BTUs present in soybeans (Mourad, 2011;Conley, 2006), 23,200 BTUs in soybean crushing, and 18,800 BTUs in Biodiesel conversion (Pradhan, 2009). 7 The product, 1 gallon of Biodiesel, contains 120,000 BTUs (TEDB, 2010).…”
Section: Biomass Refining -> Rejected Energymentioning
confidence: 99%